Learning AIDS in Singapore : a study examining the effectiveness of HIV/AIDS efficacy messages for adolescents using a multimedia approach. - Lee, Zhuomin. (2009)
In view of the growing HIV/AIDS problem amongst adolescents and adolescents’ proclivity towards high-risk sexual behavior, this study attempts to harness the potential of interactive multimedia in educating adolescents about sexual health matters. Guided by the Extended Parallel Process Model and digital gaming literature, this study used in-depth interviews to explore adolescents’ perceptions about HIV/AIDS, message components of EPPM and receptivity towards interactive multimedia platforms. The results were used to develop an interactive multimedia game. The second evaluative research consisted a quasi-experiment to pilot-test the developed multimedia game based on EPPM framework. One hundred and thirty six students completed the survey at both points in time. Results suggested that attitudes had a mediating role on intentions and efficacy was positively related with intentions to adopt HIV protective behavior. Overall, results suggest that using multimedia, guided by theoretical framework, may be an effective means to reach and effect change in adolescents. Implications are discussed.